2021
DOI: 10.1097/md.0000000000026898
|View full text |Cite
|
Sign up to set email alerts
|

Baduanjin exercise can alleviate anxiety and depression of patients with COVID-19 in Square cabin hospital

Abstract: To investigate the anxiety and depression of patients with the coronavirus disease 2019 (COVID-19) who participated in Baduanjin exercise.From February 20, 2020 to March 7, 2020, the Hospital Anxiety and Depression scale (HAD) were used to investigate the anxiety and depression levels of patients with COVID-19 who participated in Baduanjin exercise. Ninety one questionnaires were received, including 40 males and 51 females. Stepwise regression analysis was used to analyze the effects of related factors on anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…The results are consistent with other studies [ 70 73 ] showing the Baduanjin exercise has a significant effect on alleviating anxiety symptoms. For example, Yu L et al proposed that the Baduanjin exercise has a certain positive influence on COVID-19 patients in the Square cabin hospital, which is conducive to alleviating the anxiety and depression symptoms of the patients [ 72 ]. A systematic review concluded that the efficacy of Baduanjin exercise in reducing depression and anxiety symptoms in people with physical or mental illnesses [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results are consistent with other studies [ 70 73 ] showing the Baduanjin exercise has a significant effect on alleviating anxiety symptoms. For example, Yu L et al proposed that the Baduanjin exercise has a certain positive influence on COVID-19 patients in the Square cabin hospital, which is conducive to alleviating the anxiety and depression symptoms of the patients [ 72 ]. A systematic review concluded that the efficacy of Baduanjin exercise in reducing depression and anxiety symptoms in people with physical or mental illnesses [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following, title, and abstract screening (reviewers at this stage included JSC, OLA, KB, NSK, DH, GT, SCR, RH, SHE, CM, and SH), 67 articles were included for full text review. A total of 62 studies were then excluded (reviewers at this stage included DH, RH, KB, NSW, JSC, SH, and OLA) due to either having: (1) an incorrect study design (i.e., not a randomised controlled trial or observational study with a control group), (2) an incorrect patient population (patients did not have symptoms which were either chronic or persistent enough to fulfil our criteria for PVS), and (3) a pharmacological intervention [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ,…”
Section: Resultsmentioning
confidence: 99%
“…The study by Zhang et al, showed that anxiety and depression levels varied among different COVID-19 patients in the square cabin hospital, with female and lower education levels being associated with higher levels of anxiety and depression. Through the “Baduanjin” exercise, patients’ anxiety and depression were significantly relieved [ 77 ]. A systematic review of 23 studies also indicated that PA improves both physical and psychological outcomes in COVID-19 patients [ 78 ].…”
Section: Resultsmentioning
confidence: 99%